Foreign Direct Investments: impact of party affiliation on the Brazilian subnational allocation of investments - Coury, Júlia Reis (2023)
Is party affiliation an important aspect of the subnational allocation of Foreign Direct Investments (FDI) in Brazil? If important, would a governor from a more pro-business party affiliation attract more investments than a pro-labor one? Based on the availability of data from the Electronic Declaratory Registration - Foreign Direct Investment (EDR - FDI) and Quinquennial Census of Foreign Capital, both by the Brazilian Central Bank (BACEN), I examined FDI patterns from 2011 to 2016. More specifically, the research developed: a quantitative analysis of political and economic determinants for the subnational attraction of FDI; and a qualitative investigation of one state, Minas Gerais (MG), for a closer evaluation. Based on the results of the Arellano-Bond (1991) models, market size, service sector agglomeration, states\' trade dimension, and partisan affiliation, especially if the governor is from PSDB (pro-business), are relevant factors for FDI subnational allocation. In turn, the results suggested that a higher cost of bureaucracy and alignment with the presidents political party decrease FDI. The MG in-depth case refined the importance of pro-business party affiliation by characterizing the two administrations of PSDB (pro-business) and one administration of PT (pro-labor). Interviewees analyzed the role of different party affiliations in the state government, and a pro-business party impacted how the governor treated foreign investors. The party affiliation aspect was fundamental for consultants, civil servants, and lobbyists in FDI subnational allocation.